Georg Fuchs and the Social Function of Theater: notes on the book The revolution of the theater - Beatriz Magno Alves de Oliveira (Revista Brasileira de Estudos da Presença, 2021)
The article presents and discusses some of the proposals of German theater thinker Georg Fuchs (1868-1949) contained in his book The revolution of the theater: conclusions about the Munich Artists’ Theater, published in 1909. Some of Fuch’s interlocutors during his process of creating the theater are presented. As a central axis, the discussion identifies in each of Fuchs’ aesthetic proposals his perspective of understanding art based on the role it should play in society. We thus seek to not only to identify Fuchs’ aesthetic proposals, but also to emphasize, in addition to them, his political objectives.